Causal relationship between kidney stones and gut microbiota contributes to the gut-kidney axis: a two-sample Mendelian randomization study - Liu, Minghui; Zhang, Youjie; Wu, Jian; Gao, Meng; Zhu, Zewu; Chen, Hequn (Frontiers in Microbiology, 2023)
Background Gut microbiota, particularly Oxalobacter formigenes, has been previously reported to be associated with kidney stones. However, the conflicting results from both observational and intervention studies have created substantial uncertainty regarding the contribution of Oxalobacter formigenes to the formation of kidney stone.We employed a two-sample MR analysis to investigate the causal relationship between gut microbiota and kidney stones using GWASs summary statistics obtained from the MiBioGen and FinnGen consortia. Moreover, we conducted a reserve MR analysis to assess the direction of the causal associations between gut microbiota and kidney stones. The inverse variance weighted (IVW) approach represents the primary method of Mendelian Randomization (MR) analysis.Our analyses do not yield supportive evidence for a causal link between the genus Oxalobacter (OR=0.99, 95% CI: 0.90-1.09, P=0.811) and the formation of kidney stones. The order Actinomycetales (OR=0.79, 95% CI: 0.65-0.96, P=0.020), family Actinomycetaceae (OR=0.79, 95% CI: 0.65-0.96, P=0.019), family Clostridiaceae 1 (OR=0.80, 95% CI: 0.67-0.96, P=0.015), genus Clostridiumsensustricto 1 (OR=0.81, 95% CI: 0.67-0.98, P=0.030) and genus Hungatella (OR=0.86, 95% CI: 0.74-0.99, P=0.040) had protective effects on kidney stones, and the genus Haemophilus (OR=1.16, 95% CI: 1.01-1.33, P=0.032), genus Ruminococcaceae (UCG010) (OR=1.38, 95% CI: 1.04-1.84, P=0.028), genus Subdoligranulum (OR=1.27, 95% CI:1.06-1.52, P=0.009) were risk factors for kidney stones. Differential abundance analysis provide no evidence of a association between Oxalobacter formigenes and kidney stones, and showed genus Subdoligranulum were risk factors for kidney stones. Reverse MR analysis did not indicate any causal association of kidney stones on gut microbiota. No considerable heterogeneity of instrumental variables or horizontal pleiotropy was observed.Oxalobacter and kidney stones. The association between gut microbiota and kidney stones does not solely depend on the presence of genus Oxalobacter/Oxalobacter formigenes. A more integrated approach using multiple omics platforms is needed to better understand the pathogenesis of kidney stones in the context of complex gene-environment interactions over time.